ANALISIS KOMPARATIF EFEKTIVITAS IMPLEMENTASI KURIKULUM MERDEKA ANTARA SEKOLAH PENGGERAK DAN SEKOLAH NON PENGGERAK JENJANG SMP - Naomi Dillak; Tans Feliks; Marsel Robot (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The implementation of the Independent Curriculum has resulted in differences in treatment between Driving Schools (SP) receiving intensive mentoring and Non-Driving Schools (SNP) implementing the curriculum independently. This study aims to comprehensively analyze the differences in the effectiveness of the curriculum's implementation at the junior high school level in Kupang City. The research focuses on three main determinants: principal management (MKS), teacher performance (KG), and student learning outcomes (HBS). Using an observational approach with 18 principals, 36 teachers, and 483 students, data were processed through unpaired t-tests and regression analysis. Quantitative findings indicate a significant advantage (p<0.05) in Driving Schools with an average MKS score of 92.13, KG 90.83, and HBS 84.31, surpassing Non-Driving Schools which recorded MKS scores of 80.78, KG 79.63, and HBS 65.32. Data analysis demonstrates that principal management positively contributes to teacher performance and academic achievement, with the influence of principal leadership on HBS being more pronounced in the SP environment. The main conclusion of the study confirms that the effectiveness of the Independent Curriculum implementation in the Leading Schools is significantly better than in the Non-Leading Schools. This indicates that systematic training support and additional operational assistance funds in the Leading Schools program have successfully created a higher-quality learning ecosystem that is more adaptable to change. ABSTRAK Implementasi Kurikulum Merdeka memunculkan perbedaan perlakuan antara Sekolah Penggerak (SP) yang menerima pendampingan intensif dan Sekolah Non Penggerak (SNP) yang melaksanakan secara mandiri. Penelitian ini bertujuan menganalisis secara komprehensif perbedaan efektivitas implementasi kurikulum tersebut pada jenjang SMP di Kota Kupang. Fokus penelitian diarahkan pada tiga determinan utama: manajerial kepala sekolah (MKS), kinerja guru (KG), dan hasil belajar siswa (HBS). Menggunakan pendekatan observasi terhadap 18 kepala sekolah, 36 guru, serta 483 siswa, data diolah melalui uji-t tidak berpasangan dan analisis regresi. Temuan kuantitatif menunjukkan keunggulan signifikan (p<0,05) pada Sekolah Penggerak dengan rata-rata skor MKS sebesar 92,13, KG 90,83, dan HBS 84,31, melampaui Sekolah Non Penggerak yang mencatatkan skor MKS 80,78, KG 79,63, dan HBS 65,32. Analisis data membuktikan bahwa manajerial kepala sekolah berkontribusi positif terhadap kinerja guru dan prestasi akademik, dengan pengaruh KG terhadap HBS yang lebih nyata di lingkungan SP. Simpulan utama penelitian menegaskan bahwa efektivitas implementasi Kurikulum Merdeka di Sekolah Penggerak jauh lebih baik dibandingkan Sekolah Non Penggerak. Hal ini mengindikasikan bahwa dukungan pelatihan sistematis dan dana bantuan operasional tambahan pada program sekolah penggerak berhasil menciptakan ekosistem pembelajaran yang lebih berkualitas dan adaptif terhadap perubahan.